In vivo Evaluation of Substituted 3-Amino-1,4-benzodiazepines as Anti-depressant, Anxiolytic and Anti-nociceptive Agents - Lattmann, Eric; Lattmann, Pornthip; Boonprakob, Yodchai; Airarat, Wanchai; Singh, Harjit; Offel, Michael; Sattayasai, Jintana (Arzneimittelforschung, 2009)
Oxazepam (CAS 604-75-1) 4a served as building block in the synthesis of substituted 3-amino-1,4-benzodiazepines, which were subsequently tested in various CNS animal models. The hydroxy group of oxazepam was either activated as a chloride (Method A) or as a phosphor-oxy derivative (Method B) giving the desired 3-amino-1,4-benzodiapines 6a–6r in high yields with primary and secondary amines in a typical nucleophilic substitution reaction. Eighteen 3-substituted 1,4-benzodiazepines were prepared and served as new chemical entities and for lead structure discovery. The mixed cholecystokinin (CCK) antagonist 6e showed anxiolytic and antidepressant effects from 10 μg/kg in mice in the elevated x-maze test and the forced swimming test. The CCK1 antagonist 6 g has shown antidepressant effects from the same dose, but lacked anxiolytic properties. Both compounds potentiated at a dose of 0.5 mg/kg morphine antinociception with a maximum possible effect (MPE) about 35%. By assessing initially the MPE of antinocipection for the 18 newly synthesised benzodiazepines in the tail-flick test, 4 other benzodiazepines were found active. In further in vivo evaluation the cyclohexyl derivative 6i displayed anxiolytic, antidepressant and antinociceptive properties as single agent at a dose of 5 mg/kg without toxicity. The benzodiazepines 6i and 6p, which initially showed a higher MPE in terms of morphine potentiation (43/44%) showed analgesic effects as single agents, without having anxiolytic or antidepressant properties.The amino-piperidinyl derivative 6p displayed a similar dose-response relationship to morphine, but was 3 times more potent.
Keywords: 3-Amino-5-phenyl-l,4-benzodiazepinone; Antidepressants; Antinociceptives; Anxiolytics; 1,4-Benzodiazepines, template; CAS 604-75-1; Cholecystokinin antagonists; Oxazepam